Lightweight Dynamic Crypto Algorithm for Next Internet Generation - Al-Omari, A. H. (Engineering, Technology & Applied Science Research, 2019)
Modern applications, especially real time applications, are hungry for high-speed end-to-end transmission which usually conflicts with the necessary requirements of confidential and secure transmission. In this work, a relatively fast, lightweight and attack-resistant crypto algorithm is proposed. The algorithm is a symmetric block cipher that uses a secure pre-shared secret as the first step. Then, a dynamic length key is generated and inserted inside the cipher text. Upon receiving the cipher text, the receiver extracts the key from the received cipher text to decrypt the message. In this algorithm, ciphering and deciphering are mainly based on simple XoR operations followed by substitutions and transpositions in order to add more confusion and diffusion to the algorithm. Experimental results show faster encryption/decryption time when compared to known encryption standards.